Employee Performance Based on Job Satisfaction and Work Environment - Anis Anshari Mas'ud; Wahyu Maulid Adha (Universitas Sulawesi Barat, 2023)
The purpose of this study was to determine the effect of job satisfaction and work environment on employee performance. The data analysis method used is descriptive analysis and multiple linear regression analysis using the SPSS version 25 application. The data collection techniques in this study were interviews, questionnaires and observations. The population in this study amounted to 32 employees at the Parepare City Youth and Sports Department of Tourism. The sampling technique in this study was Saturated sampling. The sample in this study were 28 permanent employees and 4 non-permanent employees) at the Youth and Sports Department of Tourism of Parepare City. The results showed that Job Satisfaction has a positive and insignificant effect on performance with a regression coefficient value of 0.340 and a probability value of 0.037> 0.005. Partially job satisfaction also affects performance in terms of the t value of 2.189> t table 2.045. The work environment has a positive and significant effect on performance with a regression coefficient value of 0.554 and a probability value of 0.003 <0.005. Partially, the work environment also affects performance in terms of the t value of 3.226> t table 2.045. Job Satisfaction and Work Environment simultaneously affect performance seen from the F value of 10.797> F table 3.32.